Diet and Exercise in the Management of Polycystic Ovary Syndrome: Practical Considerations for Person-Centered Care - Colombo, Giorgia E.; Pirotta, Stephanie; Sabag, Angelo (Seminars in Reproductive Medicine, 2023)
Polycystic ovary syndrome (PCOS) is a complex multisystem condition associated with life-long reproductive, metabolic, and psychological symptoms. Individuals with PCOS are at an increased risk of cardiovascular disease and type 2 diabetes, with approximately 70% of all PCOS cases presenting with insulin resistance. Lifestyle interventions have historically been recommended as first-line therapies for the management of PCOS-related cardiometabolic disorders. The term “lifestyle management” incorporates a multifaceted approach to dietary, exercise, and behavioral strategies, aiming to promote a healthy lifestyle. This approach has been commonly employed in practice, in particular through exercise and dietary modulation, due to its effect on cardiometabolic outcomes as well as its tolerability. Furthermore, there is evidence to suggest that combining dietary change with exercise may yield the greatest improvements in clinical outcomes. However, such practices require careful consideration and coordination, as there are instances where certain exercise and/or dietary prescriptions may compromise the effectiveness of the respective interventions. Thus, this review aims to provide practical guidance on diet and exercise planning in the routine care of PCOS. Such recommendations include emphasizing realistic and achievable goals, as well as minimizing barriers to lifestyle changes in order to increase the long-term sustainability of this treatment strategy.
Keywords: polycystic ovary syndrome; exercise; diet; lifestyle medicine; realistic medicine